Efektifitas Model Pembelajaran Flipped Classroom Berbasis Youtube Sebagai Media Pembelajaran Stilistika Pascapandemi Covid-19 - Prasetyo, Heru; Putri, Ayu Setiyo; Munaris, Munaris (Aksara: Jurnal Bahasa dan Sastra, 2022)
This study tries to capture the adequacy of the use of the YouTube-based flipped classroom learning model for the Stylistics course for students of the Indonesian Language and Literature Education Study Program, FKIP University of Lampung after Covid-19. The methodology used is quantitative Pre-Experimental Design with one group pretest-posttest design. The results of this study were obtained by giving tests of the evaluation results of stylistics courses in the form of pretest and posttest. The researcher found that the impact of the ability of students of the Indonesian Language and Literature Education Study Program FKIP University of Lampung had a large increase in pre-test and post-test scores. This is indicated by the pretest value of 48.44 and the normal post-test of 67.19. In addition, it was observed that the significance value (2 tailed) was 0.000. This means that the impact is very important because 0.000 is less than 0.05 (0.000.05). This means that H0 is rejected while H1 is recognized that there is an important influence on the use of the YouTube-based flipped classroom model on students' ability to understand Stylistic material.